Una pedagogía contextual - Wernicke, Carlos G. (2003)
Based on the relationship among politics, economy and pedagogy, in individual development and the knowledge about perception, the construction of conceptual maps and paradigms, pedagogy an education are defined and a contextual pedagogy is proposed, which is described in its essence.